Analisis Kualitas Jaringan Internet Pada Pulau Rempang Galang Kota Batam - Yuli Siyamto; Asron Saputra (Politeknik Negeri Batam, 2019)
This study aims to determine the extent of the quality of cellular-based internet network services in the coastal areas of Batam, especially on Rempang Galang Island. The background of the research is to increase public awareness to use the internet for economic development and to improve the quality of human resources. With the internet, the people of Rempang Galang Island can open their insights, knowledge, skills, market share and wider business opportunities. This awareness has also led to an increase in the number of people who use cellular-based internet. With cellular-based, many advantages are obtained. Among others, it does not depend entirely on PLN electricity, mobility and flexibility and has many uses. In order to serve the needs of the Rempang Galang community for good internet network services, a study is needed to find out the facts on the ground. The research method used is the QoS (Quality Of Service) method. The main parameters of throughput, delay, packet loss, and jitter with reference standards are TIPHON (Telecommunications and Internet Protocol Harmonization over Networks). The tools used are Axis NetTools, Wireshark and Iperf. The results of the study will obtain a picture of the quality of cellular-based internet network services on Rempang Galang Island, Batam City. The final goal of the research is as input for the Batam City Government and the private sector in order to jointly build the Batam City to be more advanced and equitable.